From Consumption to Creation: The Empowerment of Millennial K-Pop Fangirls in Building Business Ventures - Anugrah Setiani, Ramadhani (Green Publisher Indonesia, 2025)
The consumerism phenomenon in K-Pop culture has reshaped cultural consumption into productive economic activities, particularly among millennial female fans. Initially perceived as highly consumptive, K-Pop fangirls allocate significant financial resources to acquiring idol-related products, often influenced by social media competition within the fandom. The desire to be recognized as ‘loyal fans’ drives them to continuously purchase merchandise and other K-Pop-related items. However, many millennial fangirls have undergone a transformation, evolving into entrepreneurs who generate substantial profits and create employment opportunities. This study examines this shift through a review of 109 literature sources from 2008 to 2024, using Bourdieu’s Social Capital Theory to analyze how fangirls leverage social networks and cultural knowledge to develop businesses. Their ventures fall into three main categories: product-based enterprises (merchandise and handmade items), service-based businesses (concert ticketing and tourism), and digital content services. Key success factors include effective digital platform utilization, strong community engagement, and cultural competence, while challenges involve operational complexities and business sustainability. This transformation represents a new entrepreneurial model that integrates fan passion, digital expertise, and community engagement, paving the way for sustainable business opportunities. The findings provide valuable insights into digital entrepreneurship, demonstrating how cultural enthusiasm can drive business innovation and suggesting new pathways for entrepreneurship based on fandom-driven economic activities.